Exogenous Melatonin Alleviates Alkaline Stress by Removing Reactive Oxygen Species and Promoting Antioxidant Defence in Rice Seedlings - Lu, Xuping; Min, Weifang; Shi, Yafei; Tian, Lei; Li, Peifu; Ma, Tianli; Zhang, Yinxia; Luo, Chengke (Frontiers in Plant Science, 2022)
Saline-alkali stress seriously restricts rice growth, developmen and production in northern China. The damage of alkaline stress on rice is much greater than that of salt due to ion toxicity, osmotic stress, and especially high pH. As a signal molecule, melatonin (N-acetyl-5-methoxytryptamine, MT) mediates many physiological processes in rice and participates in protecting rice from abiotic stress. The potential mechanism of exogenous melatonin-mediated alkaline stress tolerance is still largely unknown. In this study, the effects of melatonin on the morphological change, physiological property and corresponding genes expression in rice seedlings were analysed under alkaline stress (20 mmol·L-1, pH9.55). The results showed that the expression levels of MT synthesis genes (TDC2, T5H, SNAT, ASMT1, ASMT2) were induced in alkaline stress treated rice by MT pretreatment. The cell membrane was protected by scavenging reactive oxygen species (ROS), reducing lipoxygenase (LOX) activity and malondialdehyde (MDA) content. The scavenging of ROS by melatonin is attributed to the coupling of the improvement of redox homeostasis and the enhancement of antioxidant enzyme activity and antioxidant content by upregulating the transcriptional levels of antioxidase genes. In the meantime, MT pretreatment promoted the accumulation of free proline, sucrose, and fructose by regulating the OsP5CS, OsSUS7, OsSPS1 gene expression level and increased chlorophyll content up-regulating the expression of chlorophyll synthesis-related genes. Ultimately, the alleviating effect of exogenous melatonin on alkaline stress was reflected in increasing the leaf relative water content (RWC) and root-shoot ratio and reducing the leaf tip wilt index (TWI) through a series of physiological and biochemical changes. Melatonin pretreatment changed the expression level of MT synthesis genes which might contribute to MT synthesis in rice, consequently, activated the ROS scavenging system and alleviating the damage of alkaline stress on rice seedlings. Our study comprehensively the alleviating effect of exogenous melatonin on rice under alkaline stress.